2003
DOI: 10.21273/jashs.128.2.0171
|View full text |Cite
|
Sign up to set email alerts
|

Cytological and Ultrastructural Evaluations of Zinc Deficiency in Leaves

Abstract: Zinc deficiency is a widespread nutritional disorder in plants and occurs in both temperate and tropical climates. In spite of its physiological importance, cytological and ultrastructural changes associated with zinc deficiency are lacking, in part because zinc deficiency is difficult to induce. A method was developed to induce zinc deficiency in pecan (Carya illinoinensis (Wangenh.) C. Koch) using hydroponic culture. Zinc deficiency was evaluated in leaves using light and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Leaflet area and TCSA were significantly reduced in both levels of Zn deficiency (Table 2): leaflet area decreased by 24 and 64% in trees with chlorotic and necrotic leaves, respectively, whereas TCSA decreased by 27 and 57% in the same trees when compared to the Zn‐sufficient controls. Similar effects of Zn deficiency on growth parameters have been reported for pecan,16, 24, 34 and other fruit tree species such as peach ( Prunus persica ),35 apple ( Malus domestica )36 and mandarin ( Citrus reticulata ) 37, 38. Reductions in growth parameters with Zn deficiency have also been reported in annual species such as Phaseolus vulgaris 39 and Triticum aestivum 40…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Leaflet area and TCSA were significantly reduced in both levels of Zn deficiency (Table 2): leaflet area decreased by 24 and 64% in trees with chlorotic and necrotic leaves, respectively, whereas TCSA decreased by 27 and 57% in the same trees when compared to the Zn‐sufficient controls. Similar effects of Zn deficiency on growth parameters have been reported for pecan,16, 24, 34 and other fruit tree species such as peach ( Prunus persica ),35 apple ( Malus domestica )36 and mandarin ( Citrus reticulata ) 37, 38. Reductions in growth parameters with Zn deficiency have also been reported in annual species such as Phaseolus vulgaris 39 and Triticum aestivum 40…”
Section: Resultssupporting
confidence: 68%
“…Some Zn deficiency effects on pecan physiology have been described in a few studies, and these include a decrease in the activity of the enzyme carbonic anhydrase in leaf extracts,13 an inhibition of the development of reproductive structures,14 and a reduction in chlorophyll synthesis and photosynthesis rates 15. Leaves of pecan trees grown in hydroponics under Zn deficiency showed symptoms varying in severity, ranging from interveinal mottling to general chlorosis, necrosis and curving of leaf margins 16. Moreover, microscopy studies showed that Zn‐deficient leaves had shorter palisade cells, more intercellular spaces, reduced thickness, and decreased surface when compared to leaves containing sufficient levels of Zn 16.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc deficiency depresses plant growth especially shoot growth and chlorophyll concentrations (Balakrishnan et al, 2001), leading to chlorosis in leaves along with abnormalities in leaf structure and ultimately affecting chloroplast structure (Kim and Wetzstein, 2003). A decline in the net photosynthetic rate (P n ) induced by Zn deficiency is often observed.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency in pecans results in rosetting; interveinal chlorosis; small, chlorotic (and necrotic) leaves (Fig. 1); less cytoplasm; and failure of chloroplast formation (limiting photosynthesis) (Kim and Wetzstein, 2003).…”
Section: Visual Zinc Deficiency Ratings (1 = Severe Zinc Deficiency; mentioning
confidence: 99%